A Comparative Study on Same Day Sputum Smear Microscopy with the Conventional Method in the Diagnosis of Sputum Positive Pulmonary Tuberculosis - Mahesh Gupta; Manju Toppo; Lokendra Dave; Jeewan Singh Meena; Daneshwar Singh; Soumitra Sethia (Medsci Publications, 2017)
Introduction: The World Health Organization (WHO) declared tuberculosis(TB) as a global emergency in 1993 and still is a major health problem across the world.The basis of the WHO recommendation comes from a Meta analysis and several studies which showed same day sputum microscopy has similar diagnostic accuracy as compared to the conventional technique.The rationale behind this research is to generate evidence in favour for same day microscopy with the conventional technique in routine programme settings. Objective: Comparative assessment of same day (Spot1-Spot2) and Conventional (Spot1-Morning sputum) methods in TB suspects. Material & Method: The study was Cross sectional conducted from the 1st March 2015 to 28th Feburary.2016. Data was collected by using predesigned questionnaire for sample collection. Results: On comparison with conventional approach it was found that same day approach had sensitivity 95%, specificity 100% and PPV, NPV in same day approach are 100%, 99.03% respectively. McNemar test (p =0.074), it indicates statistically insignificant difference in the two approaches. Conclusion: Implication of same day approach helps the patients to get results and initiation of TB treatment on same day, will help to reduce the burden of TB treatment and make the programme successful in real way.